Effect of AgO loading on flame-made LaFeO3 p-type semiconductor nanoparticles to acetylene sensing - A. Sukee (2020)
© 2020 Elsevier B.V. In this work, unloaded and Ag-loaded LaFeO3 gas sensors produced using flame spray pyrolysis (FSP) for the first time were investigated for acetylene gas-sensing applications. From the structural analyses using X-ray diffraction, electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy that the formation of AgO nanoclusters on spherical LaFeO3 particles was identified. From gas-sensing measurements, the unloaded LaFeO3 sensor displayed high sensitivity and selectivity to low concentrations (< 500 ppm) of acetylene. The 0.1 wt% Ag-loaded LaFeO3 sensor gave the highest sensor signal (60) towards 100 ppm acetylene, which is almost 12 times higher than the pure material at an optimal working temperature of 200 °C. In addition, it exhibited low cross sensitivity to hydrogen, carbon monoxide, ethylene, methane and carbon dioxide. Higher Ag loading (1 wt%) resulted in low sensitivity and no selectivity to acetylene. Loading with Ag at the low content (0.1 wt%) also lowered the humidity dependence of the sensor response. Through a detailed analysis, the enhanced acetylene-sensing performance of Ag-loaded LaFeO3 could be attributed to a Fermi-level control mechanism. It was found that the FSP-made LaFeO3-based gas sensors are better than other materials for sensing low acetylene concentrations in practical applications such as the dissolved gas analysis of transformer oil.